2018
DOI: 10.1002/adhm.201801186
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Label‐Free Imaging of 3D Vascular Networks Self‐Assembled in Synthetic Hydrogels

Abstract: Vascularization is an important strategy to overcome diffusion limits and enable the formation of complex, physiologically relevant engineered tissues and organoids. Self-assembly is a technique to generate in vitro vascular networks, but engineering the necessary network morphology and function remains challenging. Here, autofluorescence multiphoton microscopy (aMPM), a label-free imaging technique, is used to quantitatively evaluate in vitro vascular network morphology. Vascular networks are generated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…There are multiple vascular imaging modalities such as OCT that can be used on small field of view, while VMI can provide the whole-organ vascular structure. Like VMI, Kaushik et al 47 performed vascular imaging using autofluorescence signal. However, Kaushik et al performed imaging on engineered tissue using synthetic hydrogel, while VMI imaged frozen rodent organs with blood and tissue around vascular structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple vascular imaging modalities such as OCT that can be used on small field of view, while VMI can provide the whole-organ vascular structure. Like VMI, Kaushik et al 47 performed vascular imaging using autofluorescence signal. However, Kaushik et al performed imaging on engineered tissue using synthetic hydrogel, while VMI imaged frozen rodent organs with blood and tissue around vascular structures.…”
Section: Discussionmentioning
confidence: 99%
“…Like VMI, Kaushik et al. 47 performed vascular imaging using autofluorescence signal. However, Kaushik et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, it has been demonstrated that non-invasive nonlinear microscopy represents a promising strategy for label-free live imaging of 3D engineered tissues. In fact, several studies had been performed to characterize morphology ( Hofemeier et al, 2016 ; Nguyen et al, 2017 ; Syverud et al, 2017 ; Costa Moura et al, 2018 ; Kaushik et al, 2019 ; Moura et al, 2019 ), functionality ( Hofemeier et al, 2016 ; Li et al, 2017 ; Syverud et al, 2017 ; Cong et al, 2019 ; Okkelman et al, 2020 ), composition and distribution of chemicals ( Hofemeier et al, 2016 ; Li et al, 2017 ; Syverud et al, 2017 ; Costa Moura et al, 2018 ; Moura et al, 2019 ; Sood et al, 2019 ), invasion, infiltration and mechano-regulation of cellular constructs ( Hofemeier et al, 2016 ; Nguyen et al, 2017 ; Syverud et al, 2017 ; Costa Moura et al, 2018 ; Kaushik et al, 2019 ; Moura et al, 2019 ; Sood et al, 2019 ), which have been collected in Table 4 . A representative study made by Hofemeier et al (2016) carried out a multi-spectral CARS and SHG imaging on an engineered bone tissue from stem cell differentiation toward osteogenic phenotype within 3 weeks of culture.…”
Section: Nonlinear Microscopy Toward 3d Bioengineered Systemsmentioning
confidence: 99%
“…To date, Moura provided a comparison between SHG and CARS imaging of collagen to highlight the difference in signal distribution and observed the synthetic constructs in their thickness. Another innovative example of label-free, vital NLO imaging in tissue engineering is the study of Kaushik et al (2019) which observed blood vessels formation in a dynamic bioreactor providing multi-well plates with media-flow re-circulation circuits. By monitoring the endogenous TPEF from the cells encapsulated and differentiated within a 3D hydrogel, they were able to reconstruct the network in its three-dimensionality.…”
Section: Nonlinear Microscopy Toward 3d Bioengineered Systemsmentioning
confidence: 99%
“…Additionally, scattering and absorption of both the visible excitation sources and emissions by the contrast agents present a challenge to 3D in vitro and in vivo imaging [6]. The development of multiphoton microscopy with pulsed near-red and infrared laser excitation sources enabled in vivo imaging of live cells and tissue structures at high resolution, low phototoxicity, and reasonable depth of penetration (300-1000 µm) [7][8][9][10][11]. Furthermore, the possibility of higher harmonic imaging by second harmonic generation (SHG) and third harmonic generation (THG) enables additional modes of endogenous tissue contrast and opportunities for development of exogenous contrast agents which report by fluorescence-independent mechanisms.…”
Section: Introductionmentioning
confidence: 99%